The challenges of living with and managing epidermolysis bullosa: insights from patients and caregivers - Bruckner, Anna L. (Orphanet J Rare Dis, 2020)
BACKGROUND: Little information is available regarding the burden of living with and managing epidermolysis bullosa, including the distinct challenges faced by patients with different disease types/subtypes. METHODS: A 90-question/item survey was developed to collect demographics, diagnostic data, management practices, and burden of illness information for patients with epidermolysis bullosa living in the United States. Recruitment was conducted via email and social media in partnership with epidermolysis bullosa patient advocacy organizations in the United States, and the survey was conducted via telephone interview by a third-party health research firm. Respondents aged ≥ 18 years with a confirmed diagnosis of epidermolysis bullosa or caring for a patient with a confirmed diagnosis of epidermolysis bullosa were eligible to participate in the survey. RESULTS: In total, 156 responses were received from patients (n = 63) and caregivers (n = 93) representing the epidermolysis bullosa types of simplex, junctional, and dystrophic (subtypes: dominant and recessive). A large proportion of patients (21%) and caregivers (32%) reported that the condition was severe or very severe, and 19% of patients and 26% of caregivers reported a visit to an emergency department in the 12 months prior to the survey. Among the types/subtypes represented, recessive dystrophic epidermolysis bullosa results in the greatest wound burden, with approximately 60% of patients and caregivers reporting wounds covering > 30% of total body area. Wound care is time consuming and commonly requires significant caregiver assistance. Therapeutic options are urgently needed and reducing the number and severity of wounds was generally ranked as the most important treatment factor. CONCLUSIONS: Survey responses demonstrate that epidermolysis bullosa places a considerable burden on patients, their caregivers, and their families. The limitations caused by epidermolysis bullosa mean that both patients and caregivers must make difficult choices and compromises regarding education, career, and home life. Finally, survey results indicate that epidermolysis bullosa negatively impacts quality of life and causes financial burden to patients and their families.